2006
DOI: 10.1152/ajpheart.00441.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic ADP ribose-mediated Ca2+signaling in mediating endothelial nitric oxide production in bovine coronary arteries

Abstract: . Cyclic ADP ribosemediated Ca 2ϩ signaling in mediating endothelial nitric oxide production in bovine coronary arteries. Am J Physiol Heart Circ Physiol 290: H1172-H1181, 2006. First published October 21, 2005 doi:10.1152/ajpheart.00441.2005.-The present study tested the hypothesis that cyclic ADP ribose (cADPR) serves as a novel second messenger to mediate intracellular Ca 2ϩ mobilization in coronary arterial endothelial cells (CAECs) and thereby contributes to endothelium-dependent vasodilation. In isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 59 publications
1
36
1
Order By: Relevance
“…The observation that responses to the endothelial-cell-specific agonist ACh were inhibited as well as the spontaneous events shows that the inhibitors did act on the endothelial cells. Although some studies have suggested that ryanodine receptors and cyclic ADP-ribose contribute to agonist-evoked increases in endothelial cell Ca 2+ increases [35,36], neither ryanodine nor nicotinamide had a significant inhibitory effect on the spontaneous endothelial Ca 2+ events in our study. This concurs with a lack of effect of ryanodine on spontaneous Ca 2+ events in rat ureter endothelial cells in situ [20].…”
Section: Release Of Ca 2+ From Endothelial Cell Intracellular Storescontrasting
confidence: 93%
“…The observation that responses to the endothelial-cell-specific agonist ACh were inhibited as well as the spontaneous events shows that the inhibitors did act on the endothelial cells. Although some studies have suggested that ryanodine receptors and cyclic ADP-ribose contribute to agonist-evoked increases in endothelial cell Ca 2+ increases [35,36], neither ryanodine nor nicotinamide had a significant inhibitory effect on the spontaneous endothelial Ca 2+ events in our study. This concurs with a lack of effect of ryanodine on spontaneous Ca 2+ events in rat ureter endothelial cells in situ [20].…”
Section: Release Of Ca 2+ From Endothelial Cell Intracellular Storescontrasting
confidence: 93%
“…Alternatively, different beta-subunit of BK channels expressed in smooth muscle cells and endothelial cells may modify the effect of peroxynitrite on BK channel activity. [38,39]. Related to this speculation is the report that H 2 O 2 has been shown to stimulate NOS and increase NO production in vessels [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…These physiological effects or pathophysiological responses may result from different Ca 2+ signalling pathways in different types of cells/organs. In bovine coronary artery, bradykinin‐induced vasodilation is related to endothelial Canormali2+ increase mediated by cyclic ADP ribose‐RyRs Ca 2+ signalling pathway, but not PLC‐IP3Rs Ca 2+ signalling pathway, because the PLC inhibitor U73122 and the IP3R inhibitor 2‐aminoethoxydiphenyl borate do not affect the Canormali2+ increase induced by bradykinin 41. However, an earlier study demonstrated that bradykinin induces an increase in inositol 1,4,5‐triphosphate (IP3) in neonatal rat cardiomyocytes42 and bradykinin‐mediated short nocifensive responses is related to activating PLC, followed by Orai1 in afferent sensory neurons 18…”
Section: Discussionmentioning
confidence: 96%